THE INFLUENCE OF PRINCIPAL TRANSFORMATIONAL LEADERSHIP, QUALITY CULTURE AND JOB SATISFACTION ON TEACHER PERFORMANCE - Wati, Radiyah; Metroyadi, Metroyadi; Suhaimi, Suhaimi (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to find out and analyze the direct and indirect influence of the principal's transformational leadership, quality culture and job satisfaction on teacher performance.  This study is correlational descriptive research with path analysis. The research sample was 92 people. Data collection was carried out using instruments consisting of transformational leadership of school principals (26 items), quality culture (30 items), job satisfaction (22 items) and teacher performance (26 items) which have been tested for validity and reliability. The data analysis of this study uses path analysis (Path Analysis). The results of the study show that there is an influence of transformational leadership of school principals and quality culture through job satisfaction on teacher performance, both directly and indirectly.